Preparation and characterization of brake linings from modified tannin-phenol formaldehyde resin and asbestos-free fillers - Mutlu, I; Alma, MH; Basturk, MA; Oner, C (Springer, 2005)
[Abstract Not Available]
Keywords: Friction Materials; Wood Adhesives; Workers